SMART GIRLS, HARD‐WORKING GIRLS BUT NOT YET SELF‐ASSURED GIRLS: THE LIMITS OF GENDER EQUITY POLITICS - Dentith, Audrey (Canadian Journal of Education/Revue canadienne de l'éducation, 2008)
Higher levels of girls and women’s participation in targeted areas are widely apparent, particularly in affluent and middle‐class sites. Here, we report on research with young middle and upper middle‐class high school girls successfully enrolled in non‐traditional advanced placement (AP) courses in mathematics, science, and computer programming in a suburban school district in Midwestern USA. Focus group inter‐views with 45 of the highest achieving students in this affluent suburb revealed salient inequities and lingering impediments in the struggle for women’s equality. Likewise, the limitations of gender equity politics are evident in the co‐ opting of discourse of privilege and individualism. Key words: girls’ achievement, secondary schools, girls in advanced placement study, AP classes Une présence accrue des filles dans les cours avancés de mathématiques, de science et d’informatique au secondaire est manifeste, surtout dans les milieux aisés aux É.‐U. et dans d’autres pays occidentaux. Cette recherche quantitative, effectuée auprès de jeunes filles de classe moyenne ou supérieure inscrites dans des cours de niveau avancé de mathématiques, de science et d’informatique au secondaire dans un arrondissement scolaire du Midwest américain, révèle des inégalités importantes et des obstacles persistants dans la lutte des femmes pour une pleine égalité, ce qui montre les limites des politiques en faveur de l’équité entre les sexes. Mots clés : équité entre les sexes, filles et mathématiques avancées, cours de science, cours d’informatique, filles et science, cours de mathématiques